Chamaecrista (Leguminosae) of the Diamantina Plateau, Minas Gerais, Brazil, with six new species and taxonomic novelties - Cota, Matheus Martins Teixeira; Rando, Juliana Gastaldello; Mello-Silva, Renato (Phytotaxa, 2020)
Floras are still important for modern biodiversity studies, as they generate basic information, as well as improve understanding on the diversity of an area. This study aimed to the taxonomic study of the species of Chamaecrista from the Diamantina Plateau in Minas Gerais, Brazil, discussing morphological characteristics of the species and presenting taxonomic novelties. The work was based on the survey of herbaria collections, literature review and field expeditions. Descriptions, an identification key, illustrations of diagnostic features, photographic plates, and commentaries are presented for the 64 species of Chamaecrista from the Diamantina Plateau. Six new species are described, two lectotypifications (C. aurivilla and C. brachystachya) and one neotypification are made (C. echinocarpa), 11 new synonyms and taxonomic changes are proposed for C. astrochiton, C. claussenii, C. echinocarpa, C. exsudans, C. multipennis, and C. orbiculata. Chamaecrista sect. Xerocalyx is treated as a species complex with four taxa although more studies are needed to better understand this group.